2017
DOI: 10.1080/10717544.2017.1359703
|View full text |Cite|
|
Sign up to set email alerts
|

An injectable in situ gel with cubic and hexagonal nanostructures for local treatment of chronic periodontitis

Abstract: Periodontitis is a chronic bacterial infection, and its effective treatment is dependent on the retention of antibiotics of effective concentrations at the periodontal pockets. In this study, a solution-gel based inverse lyotropic liquid crystalline (LLC) system was explored to deliver metronidazole to the periodontal pockets for local treatment of periodontitis. It was found that the metronidazole-loaded LLC precursor spontaneously transformed into gel in the presence of water in the oral cavity. The low visc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
23
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 46 publications
(23 citation statements)
references
References 49 publications
0
23
0
Order By: Relevance
“…Therefore, careful consideration is still recommended before administering antibiotics. Anaerobic and facultative anaerobes are the main pathogens causing periodontal infection, and the local application of nitroimidazole drugs has a therapeutic effect in chronic periodontitis (136). Previous studies have reported that supportive treatment with prophylactic antibiotics and mouthwash improves implant survival and reduces postoperative complications (78).…”
Section: Systemic or Local Adjuvant Therapymentioning
confidence: 99%
“…Therefore, careful consideration is still recommended before administering antibiotics. Anaerobic and facultative anaerobes are the main pathogens causing periodontal infection, and the local application of nitroimidazole drugs has a therapeutic effect in chronic periodontitis (136). Previous studies have reported that supportive treatment with prophylactic antibiotics and mouthwash improves implant survival and reduces postoperative complications (78).…”
Section: Systemic or Local Adjuvant Therapymentioning
confidence: 99%
“…Lyotropic liquid crystalline (LLC) is self-assembled nanostructured gel that can be formed by amphiphilic lipids and surfactant in aqueous environment (Wang et al, 2019). It has multiple crystal structures, that is, lamellar, cubic and hexagonal (Qian et al, 2015;Mei et al, 2017a). The special structures provide incorporation of drugs with different solubility, including hydrophilic, hydrophobic and amphiphilic molecules (Conn & Drummond, 2013;Rajabalaya et al, 2017) and also tunable release rate (Rizwan & Boyd, 2015;Abd-Allah et al, 2016;Huang & Gui, 2018).…”
Section: Introductionmentioning
confidence: 99%
“…The special structures provide incorporation of drugs with different solubility, including hydrophilic, hydrophobic and amphiphilic molecules (Conn & Drummond, 2013;Rajabalaya et al, 2017) and also tunable release rate (Rizwan & Boyd, 2015;Abd-Allah et al, 2016;Huang & Gui, 2018). LLC exhibits perfect performance on mucosal (Huang et al, 2017), transdermal (Peng et al, 2015;Musa et al, 2017), periodontal (Mei et al, 2017a;Zheng et al, 2018), subcutaneous (Mei et al, 2017b) and other parenteral drug delivery (Wan et al, 2015;Qin et al, 2016), due to its high drug-loading capacity, appropriate viscoelasticity and good biocompatibility (Abd-Allah et al, 2016;Kulkarni & Thareja, 2016).…”
Section: Introductionmentioning
confidence: 99%
“…Researchers have tried to use liquid crystalline as drug carriers in the treatment of periodontal disease. For example, the precursor system of liquid crystalline phase containing propolis microparticles [ 26 ] and metronidazole [ 27 ] were prepared and characterized. The rheology of systems revealed properties that favored easy injection into the periodontal pocket and subsequent stable retention therein.…”
Section: Introductionmentioning
confidence: 99%